2016
DOI: 10.5090/kjtcs.2016.49.s1.s37
|View full text |Cite
|
Sign up to set email alerts
|

Projections of Demand for Cardiovascular Surgery and Supply of Surgeons

Abstract: BackgroundWhile demand for cardiovascular surgery is expected to increase gradually along with the rapid increase in cardiovascular diseases with respect to the aging population, the supply of thoracic and cardiovascular surgeons has been continuously decreasing over the past 10 years. Consequently, this study aims to achieve guidance in establishing health care policy by analyzing the supply and demand for cardiovascular surgeries in the medical service area of Korea.MethodsAfter investigating the actual numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 8 publications
0
10
0
2
Order By: Relevance
“…Based on the number of cardiac surgery-related patients and the 2040 population estimate, cardiac surgery demand for each region was projected (please refer to the study by Lee et al [13], which is included in the same volume of this journal, for the method of demand projection). Regional cardiac surgery center models that could be applied to each region were proposed based on the 6 treatment areas (excluding the metropolitan area) and the projected cardiac surgery demand.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the number of cardiac surgery-related patients and the 2040 population estimate, cardiac surgery demand for each region was projected (please refer to the study by Lee et al [13], which is included in the same volume of this journal, for the method of demand projection). Regional cardiac surgery center models that could be applied to each region were proposed based on the 6 treatment areas (excluding the metropolitan area) and the projected cardiac surgery demand.…”
Section: Resultsmentioning
confidence: 99%
“…Population projection data from Statistics Korea and medical expenses data from the Health Insurance Review and Assessment Service were used for these predictions. Detailed results of demand projections can be found in the study by Lee et al [13], which is included in the same issue of this journal.…”
Section: Methodsmentioning
confidence: 99%
“…This study also demonstrated odds ratios of in-hospital mortality equal to 3.17 in Acute Kidney Injury Network (AKIN) stage 1 and 43.77 in AKIN stage 3. Given that over one million patients undergo cardiac surgery each year, CSA-AKI presents a significant burden of disease [ 2 ].…”
Section: Background and Rationale {6a}mentioning
confidence: 99%
“…Study data was collected and managed using REDCap electronic data capture tool hosted and managed by Helix (Monash University) [ 39 , 40 ]. REDCap is a secure, web-based software platform designed to support data capture for research studies, providing [ 1 ] an intuitive interface for validated data capture [ 2 ]; audit trails for tracking data manipulation and export procedures [ 3 ]; automated export procedures for seamless data downloads to common statistical packages; and [ 4 ] procedures for data integration and interoperability with external sources.…”
Section: Data Collection and Managementmentioning
confidence: 99%
“…Esta requiere de una ardua preparación con la finalidad de optimizar el abordaje del paciente [2,3] . Antiguamente, se requería alrededor de 10 años de capacitación para alcanzar dicha subespecialidad, que incluye el entrenamiento en cirugía general (por tres años), cirugía de tórax y cardiovascular (por cinco años) y CCP (por dos años) [3][4][5] . En la actualidad, en el Perú no es necesario realizar el entrenamiento previo en cirugía general, por lo que los años de entrenamiento se reducirían aproximadamente a siete años.…”
Section: Introductionunclassified